Trifluoperazine and Its Analog Suppressed the Tumorigenicity of Non-Small Cell Lung Cancer Cell; Applicability of Antipsychotic Drugs to Lung Cancer Treatment - Jeong, Joo Yeon; Park, Haangik; Yoo, Hong; Kim, Eun-Jin; Jeon, Borami; Lee, Jong Deog; Kang, Dawon; Lee, Changjoon Justin; Paek, Sun Ha; Roh, Eun Joo; Yi, Gwan-Su; Kang, Sang Soo (MDPI AG, 2022)
Despite significant advances in diagnostic and therapeutic technologies, lung cancer remains the leading cause of cancer-related mortality worldwide. Non-small cell lung cancer (NSCLC) accounts for approximately 85% of lung cancer cases. Recently, some antipsychotics have been shown to possess anticancer activity. However, the effects of antipsychotics on NSCLC need to be further explored. We examined the effects of trifluoperazine (TFP), a commonly used antipsychotic drug, and its synthetic analogs on A549 human lung cancer cells. In addition, cell proliferation analysis, colony formation assay, flow cytometry, western blot analysis, and in vivo xenograft experiments were performed. Key genes and mechanisms possibly affected by TFP are significantly related to better survival outcomes in lung cancer patients. Treatment with TFP and a selected TFP analog 3dc significantly inhibited the proliferation, anchorage-dependent/independent colony formation, and migration of A549 cells. Treatment with 3dc affected the expression of genes related to the apoptosis and survival of A549 cells. Treatment with 3dc promoted apoptosis and DNA fragmentation. In all experiments, including in vivo studies of metastatic lung cancer development, 3dc had more substantial anticancer effects than TFP. According to our analysis of publicly available clinical data and in vitro and in vivo experiments, we suggest that some kinds of antipsychotics prevent the progression of NSCLC. Furthermore, this study indicates a synthetic TFP analog that could be a potential therapeutic for lung cancer.